Catch composition and diversity of small-scale fisheries around mangrove ecosystems in Pangandaran, West Java, Indonesia - IZZA MAHDIANA APRILIANI; TOSHIMORI TAKAHASHI (Society for Indonesian Biodiversity, 2026)
Abstract. Apriliani IM, Takahashi T. 2026. Catch composition and diversity of small-scale fisheries around mangrove ecosystems in Pangandaran, West Java, Indonesia. Biodiversitas 27 (8): d270803. https://doi.org/10.13057/biodiv/d270803. Pangandaran District is an area in southern West Java that has a mangrove ecosystem and serves as a fishing ground. However, there is currently no baseline data on catch yields from small-scale fisheries in and around mangrove ecosystems. This study aims to analyze the composition, diversity and commodity status of fishermen's catches in the Pangandaran mangrove ecosystem. The mangrove ecosystems in this region are located at four sites: Babakan, Bojongsalawe, Batukaras, and Nusawiru. The research was conducted from September 2025 to January 2026 by collecting data on catches from fishermen using cast nets, traps, and handlines, with sampling conducted once every two weeks around the mangrove ecosystem. A total of 27 catch taxa from 20 families and 954 individuals were recorded, consisting of fish, shrimp, and crabs. Among the recorded taxa, 13 species were categorized as the main catch with high economic value. The diversity index (H') ranged from 2.288 to 2.742, the evenness index (E) from 0.740 to 0.842, the dominance index (C) from 0.049 to 0.122, and the species richness index (d) from 3.363 to 4.466, indicating that the catch community is in the moderate diversity category with low dominance. Descriptive Bray-Curtis similarity analysis indicated differences in catch composition among the four locations, with Batukaras and Nusawiru showing higher similarity compared to Babakan and Bojongsalawe. These differences may reflect qualitative differences in habitat condition and fishing-ground characteristics. This study provides a descriptive baseline inventory of catch composition and diversity at the Pangandaran mangrove ecosystem to support monitoring and management of small-scale fisheries.